2017
DOI: 10.1038/bcj.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Addition of cyclophosphamide and higher doses of dexamethasone do not improve outcomes of patients with AL amyloidosis treated with bortezomib

Abstract: Bortezomib, in combination with dexamethasone (VD) or with the addition of cyclophosphamide (VCD), is highly effective in patients with amyloid light-chain (AL) amyloidosis. Currently, VCD is considered as a primary regimen for patients with AL, but it is not clear whether the addition of cyclophosphamide to VD further and significantly improves efficacy, given the substantial activity of bortezomib itself. We retrospectively compared the outcomes of 101 patients with AL amyloidosis who received VD (n=59) or V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
(31 reference statements)
0
15
0
2
Order By: Relevance
“…A recent study compared the effects of treating 101 patients with AL amyloidosis with VD (59 patients) or VCD (42 patients). The results indicate that for the VD regimen, low dexamethasone doses were equally as effective as higher doses; furthermore, efficacy was not improved by the addition of cyclophosphamide (VCD) [ 96 ]. A hematologic response was achieved in 68% of patients treated with VD and 78% treated with VCD ( p = 0.26).…”
Section: Bortezomib In Light Chain Amyloidosismentioning
confidence: 99%
“…A recent study compared the effects of treating 101 patients with AL amyloidosis with VD (59 patients) or VCD (42 patients). The results indicate that for the VD regimen, low dexamethasone doses were equally as effective as higher doses; furthermore, efficacy was not improved by the addition of cyclophosphamide (VCD) [ 96 ]. A hematologic response was achieved in 68% of patients treated with VD and 78% treated with VCD ( p = 0.26).…”
Section: Bortezomib In Light Chain Amyloidosismentioning
confidence: 99%
“…Melphalan is more effective in patients harboring t(11;14) and, combined with bortezomib, it is associated with a longer response [31]. Of note, a retrospective study showed that the addition of cyclophosphamide and a combination with higher doses of dexamethasone do not significantly improve the response rate or survival of patients treated with bortezomib [32].…”
Section: Upfront Conventional Treatmentmentioning
confidence: 99%
“…We filtered a total of 1,406 articles, from which sixteen studies (Jaccard et al, 2008;Gibbs et al, 2009;Gillmore et al, 2009;Wechalekar et al, 2010;Wechalekar et al, 2013;Palladini et al, 2014;Venner et al, 2014;Kastritis et al, 2015;Milani et al, 2015;Gertz et al, 2016;Katoh et al, 2016;Kastritis et al, 2016;Milani et al, 2017;Kastritis et al, 2017;Shimazaki et al, 2018;Liu et al, 2019) involving 3,402 participants were ultimately selected for the analysis. Of the sixteen studies, three were RCTs Kastritis et al, 2016), two were prospective types (Wechalekar et al, 2010;Palladini et al, 2014), the other two were case-control types (Palladini et al, 2014;Milani et al, 2015), and the remaining nine were retrospective types Wechalekar et al, 2010;Wechalekar et al, 2013;Venner et al, 2014;Kastritis et al, 2015;Katoh et al, 2016;Kastritis et al, 2017;Shimazaki et al, 2018;Liu et al, 2019). The PRISMA flow diagram was presented in Figure 1.…”
Section: Baseline Characteristics Of Enrolled Studiesmentioning
confidence: 99%